FAKTOR-FAKTOR PENETAPAN TARIF PARKIR BERLANGGANAN KENDARAAN BERMOTOR DI KABUPATEN SIDOARJO - GANDA MIHARDJA, NOVENDRA Ganda (Jurnal Akuntansi AKUNESA, 2013)
The purpose of this research was to determine the factors that considered in the determination ofthe subscription rates of motor vehicle parking in Sidoarjo regency. The method used isdescriptive qualitative.This method is trying to describe about the factors that considered in thedetermination of the subscription rates of motor vehicle parking in Sidoarjo regency. The resultsof this study indicate that the factors considered in setting parking rates in the district ofSidoarjo are subscribed to the principle, justice, and ability.Keywords : factors, parking rates, principle, justice, ability